ERYTHROCYTES FUNCTIONAL FEATURES IN THE 11-YEAR SOLAR CYCLE - Parshina, S. S.; Tokayeva, L. K.; Dolgova, E. M.; Afanas’yeva, T. N.; Samsonov, S. N.; Petrova, V. D.; Vodolagina, E. S.; Kaplanova, T. I.; Potapova, M. V. (Одеські астрономічні публікації, 2017)
There had been studied features of rheological blood failures in patients with unstable angina (UA) in periods of the high (HSA) and low solar activity (LSA) in the 23rd 11-year solar cycle. This category of patients is characterized by prethrombotic blood state, although they don’t have coronary thrombosis. The research aimed to study compensatory mechanisms which block thrombosis development at the solar activity increase. There had been established that the period of the solar activity increasing in the 11-year solar cycle is characterized by an increase of a blood viscosity, comparing with the period of a low solar activity. Though, erythrocytes functional features in this case are compensatory mechanisms – erythrocyte aggregation paradoxically reduced and their deformability increases. It is probably connected with the revealed fibrinogen decrease in the period of the high solar activity. We can see that the change of a solar activity is accompanied not only by the progressing of pathologic processes, but also by an activation of adaptive changes in erythrocyte membrane so0 as to prevent thrombosis. Though, the required compensatory mechanisms were found invalid, which were shown in the decrease of an oxygen delivery to tissues, and the effectiveness decrease of the medical treatment in the period of a HSA.